A Novel Rice Cytochrome P450 Gene, CYP72A31, Confers Tolerance to Acetolactate Synthase-Inhibiting Herbicides in Rice and Arabidopsis . Issue 3 (9th January 2014) - Saika, Hiroaki; Horita, Junko; Taguchi-Shiobara, Fumio; Nonaka, Satoko; Nishizawa-Yokoi, Ayako; Iwakami, Satoshi; Hori, Kiyosumi; Matsumoto, Takashi; Tanaka, Tsuyoshi; Itoh, Takeshi; Yano, Masahiro; Kaku, Koichiro; et al.
Abstract : A novel cytochrome P450 monooxygenase is involved in multiple-herbicide detoxification and could be useful in herbicide development and molecular breeding in crops . Abstract: Target-site and non-target-site herbicide tolerance are caused by the prevention of herbicide binding to the target enzyme and the reduction to a nonlethal dose of herbicide reaching the target enzyme, respectively. There is little information on the molecular mechanisms involved in non-target-site herbicide tolerance, although it poses the greater threat in the evolution of herbicide-resistant weeds and could potentially be useful for the production of herbicide-tolerant crops because it is often involved in tolerance to multiherbicides. Bispyribac sodium (BS ) is an herbicide that inhibits the activity of acetolactate synthase. Rice ( Oryza sativa ) of the indica variety show BS tolerance, while japonica rice varieties are BS sensitive. Map-based cloning and complementation tests revealed that a novel cytochrome P450 monooxygenase, CYP72A31, is involved in BS tolerance. Interestingly, BS tolerance was correlated with CYP72A31 messenger RNA levels in transgenic plants of rice and Arabidopsis ( Arabidopsis thaliana ). Moreover, Arabidopsis overexpressing CYP72A31 showed tolerance to bensulfuron-methyl (BSM ), which belongs to a different class of acetolactate synthase-inhibiting herbicides, suggesting that CYP72A31 can metabolize BS and BSM to a compound with reduced phytotoxicity. On the other hand, we showed that the cytochrome P450 monooxygenase CYP81A6, which has been reported to confer BSM tolerance, is barely involved, if at all, in BS tolerance, suggesting that the CYP72A31 enzyme has different herbicide specificities compared with CYP81A6. Thus, the CYP72A31 gene is a potentially useful genetic resource in the fields of weed control, herbicide development, and molecular breeding in a broad range of crop species.